Impact of Occupational Activities on Fingerprint - da Cruz, Luismar Barbosa; Garcia, Marlon Rodrigues [UNESP]; Moriyama, Lilian Tan; Bagnato, Vanderlei Salvador; Pratavieira, Sebastião (Institute of Electrical and Electronics Engineers (IEEE), 2025)
Fingerprint biometrics are trusted globally for their precision, but what happens when skin undergoes abrupt changes? This study explores how occupational exposure alters fingerprint structures, affecting biometric reliability. Using Optical Coherence Tomography (OCT), the finger skin of 21 adults from three occupations: educators, mechanics, and cleaning staff, was scanned. Results show visible deformation of fingerprint minutiae, thinning of the stratum corneum, and increased epidermal thickness in those exposed to physical stressors. These changes highlight the impact of occupation on biometric identity. OCT proves a promising, non-invasive tool for detecting skin alterations, advancing dermatological research and secure identification.